Effect of Medial Opening Wedge and External Rotational Humeral Osteotomies on Medial Elbow Compartment Pressure: An Ex Vivo Study - Crystal, Ed; Brettle, Alice; Maddox, Thomas W.; Jones, Dan; Walton, Myles Benjamin (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective The aim of this study was to assess if the level of osteotomy (50 or 75% the length of the humerus), osteotomy angle (5, 10, or 20 degrees), direction of bone alteration (external rotational or medial opening wedge osteotomies), or orientation of osteotomy (perpendicular to the humeral long axis or perpendicular to the weight-bearing axis of the limb) affect pressure through the medial compartment of the elbow.Study Design Humeral osteotomies were performed at 50 and 75% the length of the humerus on 12 canine cadaver thoracic limbs and patient-specific three-dimensional (3D) printed plates applied to induce the desired alteration. Sensors were placed into the medial and lateral aspects of the elbow joint and the limb compressed to 90 N in a universal testing system.Results Increasing the angle of the induced change had a significant effect on the decreased load through the medial compartment. Performing the osteotomy at 75% of humeral length from proximal was significantly more effective at reducing the medial elbow load than performing it at 50%. Opening wedge osteotomies were more effective than external rotational osteotomies, but both were effective. Changing the direction of the osteotomy (comparing transverse to oblique) did not significantly affect the load reduction through the medial compartment.Conclusion Performing an osteotomy at a more distal location along the humerus and increasing the angle of the induced change increased the effectiveness of load-shifting humeral osteotomies.
Keywords: elbow dysplasia; medial compartment disease; humeral osteotomy; load-shifting; canine